Relationships between race performance and cycle characteristics in cross-country skiing: Focusing on the men's 10-km classic race - Fujita, Z.; Ishige, Y.; Yoshioka, S.; Takeda, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
The purpose of this study was to evaluate the relationships between race performance and cycle characteristics in a 10-km classic-style men's cross-country ski competition. The subjects were competitors in the 89th Japan National Ski Championships. Skiing motions of the subjects on flat stretches (1.5 km and 6.5 km) and uphill slopes (1.7 km and 6.7 km) were videotaped using two high-speed cameras. Cycle characteristics were calculated based on measurement of hip displacement and cycle time. It was revealed that elite competitors (1) performed at high velocity at all measurement points, (2) reduced their velocity in the last half of the race, (3) achieved a high velocity in double poling and diagonal stride, (4) increased their cycle length and cycle rate when employing the double poling technique, and (5) increased their cycle length when employing the diagonal stride technique.